2013
DOI: 10.1155/2013/453980
|View full text |Cite
|
Sign up to set email alerts
|

Online Spectroscopic Study on the Positive and the Negative Electrolytes in Vanadium Redox Flow Batteries

Abstract: Traditional spectroscopic analysis based on the Beer-Lambert law cannot analyze the analyte with high concentration and interference between different compositions, such as the electrolyte in vanadium redox flow batteries (VRBs). Here we propose a new method for online detection of such analytes. We demonstrate experimentally that, by comparing the transmittance spectrum of the analyte with the spectra in a preprepared database using our intensity-corrected correlation coefficient (ICCC) algorithm, parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Transmission spectra utilizes the entire spectrum range and has a better signal to noise ratio. Liu et al [161,162] utilized an in-house built transmission spectrum analytical system with a customized adsorption cell with two glass windows to allow electrolyte flow. Zhang et al [160] employed the on-line electrolyte spectroscopic monitoring configuration.…”
Section: Spectroscopic Measurement Methodsmentioning
confidence: 99%
“…Transmission spectra utilizes the entire spectrum range and has a better signal to noise ratio. Liu et al [161,162] utilized an in-house built transmission spectrum analytical system with a customized adsorption cell with two glass windows to allow electrolyte flow. Zhang et al [160] employed the on-line electrolyte spectroscopic monitoring configuration.…”
Section: Spectroscopic Measurement Methodsmentioning
confidence: 99%
“…The homemade online optical detecting module has been used to detect the transmitted light intensity of the positive electrolyte in our previous work. Because of the interactions between VO 2+ and VO 2 + ions at high concentrations in VFBs, the transmitted light intensity of the positive electrolyte does not obey Beer’s law and there is not a linear relationship between its transmitted light intensity and composition. , But when the VO 2 + is reduced to VO 2+ totally (at the electrolysis termination), we could get the total amount of substance of vanadium ions in the positive electrolyte by detecting the transmitted light intensity of the VO 2+ solution. And the amount of substance of VO 2 + is obtained by calculating the charge consumed by electrolysis based on Faraday’s laws.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Equally, soluble solids were successfully predicted by VIS/NIR spectroscopic method in different fruits -apple, kiwi. In apples the highest correlation coefficient was 0.98, depending on the number of principal components and the pre-processing techniques (Liu, Zhou, 2013). Qiang et al (2010) used NIR spectroscopy for dry matter determination in kiwifruit and reported that it could be determined non-destructively and dry matter can be predicted with very good accuracy and high correlation coefficient (r = 0.902).…”
Section: Figure 2 Amount Of Soluble Solids (°Brix) At Different Ripementioning
confidence: 99%